Differential activation of neuroinflammatory pathways in children with seizures: A cross-sectional study. (October 2021) - Bartolini, Luca; Moran, Michael P.; Norato, Gina; Thomas, Bobbe; Dick, Alexander D.; Wells, Elizabeth; Suslovic, William; Bumbut, Adrian; Chamberlain, James M.; Theodore, William H.; Gaillard, William D.; Jacobson, Steven
Highlights: CCL11 levels correlate with clinical variables of epilepsy severity. CCL11, CCL26, IL6, IL8, IL10, MIP-1β levels higher in children with seizures. IFNγ, CXCL10, IL10 levels higher in febrile seizures. No correlation for plasma/saliva cytokine levels. Frequency of HHV-6 and EBV DNA detection similar across seizure types and controls. Abstract: Purpose: Inflammation plays a crucial role in epileptogenesis. We analyzed inflammatory cytokines in plasma and saliva from children with seizures and healthy controls and measured their associations with HHV6 and EBV infection. Methods: We analyzed plasma from 36 children within 24 h of seizures (cases) and 43 healthy controls and saliva from 44 cases and 44 controls with a multiplex immunoassay. Saliva from all controls and 65 cases and blood from 26 controls and 35 cases were also analyzed by PCR for viral DNA. Primary outcome was cytokine levels in cases vs. controls. Secondary outcomes included detection of HHV-6 and EBV viral DNA in cases vs. controls and viral loads in cases vs. controls. Statistical analysis included the Wilcoxon Rank Sum test, Fisher's exact test, ANOVA, and Spearman correlation. Results: Compared to controls, patients had higher levels of CCL11 ( p  = 0.0018), CCL26 ( p <0.001), IL10 ( p  = 0.044), IL6 ( p <0.001), IL8 ( p  = 0.018), and MIP1β ( p  = 0.0012). CCL11 was higher with 3 or more seizures ( p  = 0.01), seizures longer than 10 min ( p  = 0.001), and when EEG showed focal slowing ( p  = 0.02). In saliva, febrile seizures had higher levels of IL-1β ( n  = 7, p  = 0.04) and new onset seizures had higher IL-6 ( n  = 15, p  = 0.02). Plasma and saliva cytokine levels did not show a correlation. The frequency of HHV-6 and EBV detection was similar across groups and not different than controls. We found no correlation between viral load and cytokine levels. Conclusions: We showed differential activation of neuroinflammatory pathways in plasma from different seizure etiologies compared to controls, unrelated to viral infection.